Chimney-Graft as a Bail-Out Procedure for Endovascular Treatment of an Inflammatory Juxtarenal Abdominal Aortic Aneurysm - Francesca Fratesi; Ashok Handa; Raman Uberoi; Ediri Sideso (Case Reports in Vascular Medicine)
Inflammatory and juxtarenal Abdominal Aortic Aneurysm (j-iAAA) represents a technical challenge for open repair (OR) due to the peculiar anatomy, extensive perianeurysmal fibrosis, and dense adhesion to the surrounding tissues. A 68-year-old man with an 11 cm asymptomatic j-iAAA was successfully treated with elective EVAR and chimney-graft (ch-EVAR) without postprocedural complications. Target vessel patency and normal renal function are present at 24-month follow-up. The treatment of j-iAAA can be technically challenging. ch-EVAR is a feasible and safe bail-out method for elective j-iAAA with challenging anatomy.